2009
DOI: 10.1111/j.1600-0722.2009.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional estrogen receptors alpha and beta are expressed in normal human salivary gland epithelium and apparently mediate immunomodulatory effects

Abstract: Salivary gland epithelial cells (SGECs) have been shown to participate in immunological responses and have been implicated in the pathogenesis of Sjögren's syndrome (SS). Experimental evidence from animal models indicates that estrogen deficiency may also participate in SS pathogenesis. However, the expression and functionality of the estrogen receptors alpha (ERalpha) and beta (ERbeta) in normal human salivary epithelium is unknown. To investigate these points, formalin-fixed, paraffin-embedded specimens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
(64 reference statements)
1
34
0
2
Order By: Relevance
“…Estrogen has a role in regulating epithelial maturation; thus, the decreased level of estrogen hormone such as found in post-menopausal women contributes to reduced epithelial cell maturation, leading to a thinning epithelium and atrophy. Thus, it is common to find postmenopausal women who suffer from discomfort in oral mucosa and reduced saliva secretion [4].…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen has a role in regulating epithelial maturation; thus, the decreased level of estrogen hormone such as found in post-menopausal women contributes to reduced epithelial cell maturation, leading to a thinning epithelium and atrophy. Thus, it is common to find postmenopausal women who suffer from discomfort in oral mucosa and reduced saliva secretion [4].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Tsinti et al (18) reported the absence of an impact of estrogen on cell apoptosis in vitro via salivary gland cell culture. These differences in observation may be attributed to the more complicated in vivo environment when compared with the in vitro environment (29,45,46).…”
Section: Figmentioning
confidence: 99%
“…SMG removal (sialoadenectomy) increased estrogen production and uterine weight; on the other hand, ovarian estrogen could be inhibited by the submandibular gland via inhibition of ovarian androgen production (17). Additionally, the expression of estrogen receptors (predominantly ERβ) is higher in the submandibular gland when compared with the other major salivary glands, thus implicating the role of salivary glands in the development and/or regeneration of reproductive organs and peripheral organs (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Salivary glands are not classic target organs of female sex hormones, but the influence of these hormones on these glands has been studied [4][5][6][7]; however, knowledge concerning this interaction remains scarce.…”
Section: Introductionmentioning
confidence: 99%